2019
DOI: 10.1073/pnas.1910157116
|View full text |Cite|
|
Sign up to set email alerts
|

A field experiment on community policing and police legitimacy

Abstract: Despite decades of declining crime rates, longstanding tensions between police and the public continue to frustrate the formation of cooperative relationships necessary for the function of the police and the provision of public safety. In response, policy makers continue to promote community-oriented policing (COP) and its emphasis on positive, nonenforcement contact with the public as an effective strategy for enhancing public trust and police legitimacy. Prior research designs, however, have not leveraged th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 38 publications
3
95
1
1
Order By: Relevance
“…Such shootings are only the highly visible top of a spectrum of perceived police abuses of authority, beginning with asserting dominance via demeaning, disrespectful, and harassing treatment and escalating to involve the use of clubs, tasers, and, in some cases, guns. The justifiability of any particular instance of the use of force can be debated, but there have been a number of suggestions that the police in America today overuse command and control techniques, which emphasize dominance via the threat or use of force, and that better strategies for managing interactions with the public in ways which build public trust and deescalate hostility and conflict need to be identified and incorporated into American policing (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Such shootings are only the highly visible top of a spectrum of perceived police abuses of authority, beginning with asserting dominance via demeaning, disrespectful, and harassing treatment and escalating to involve the use of clubs, tasers, and, in some cases, guns. The justifiability of any particular instance of the use of force can be debated, but there have been a number of suggestions that the police in America today overuse command and control techniques, which emphasize dominance via the threat or use of force, and that better strategies for managing interactions with the public in ways which build public trust and deescalate hostility and conflict need to be identified and incorporated into American policing (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The standard approach is to measure instrumental police-citizen relations using items like 'I only obey police because I am afraid of them ' (Posch et al, 2020) and 'What is the likelihood that you be caught and punished if you bought something you think might be stolen?' (Sunshine & Tyler, 2003) and normative police-citizen relations using items like 'You should do what the police tell you, even if you disagree' (Jackson et al, 2012), 'Obeying the law ultimately benefits everyone in the community' (Gur & Jackson, 2020), 'The police usually act in ways consistent with your own ideas about what is right or wrong' (Peyton et al, 2019), 'I trust the leaders of the NYPD to make decisions that are good for everyone in the city' (Tyler & Fagan, 2008), and 'How wrong is it to buy something you think might be stolen?' (Trinkner et al, 2018).…”
Section: (2) Are Motivations To Comply With the Law Distinct From Eacmentioning
confidence: 99%
“…It could also be that some police activities were more likely to be seen as reconciliatory gestures designed to repair past harm, which O'Brien et al (in press) argued can be impactful in building trust. Peyton et al (2019) found that racial minorities and those with lower trust in police at baseline were most impacted by the intervention. This is consistent with work by Murphy, Cherney, and Teston (2019), who argued that those who felt most excluded from society (in their study, the focus was on Muslim Australians) reacted most positively to being treated fairly by police.…”
Section: Procedural Justice In Community Engagement Projectsmentioning
confidence: 94%